Osmotic demyelination syndrome in a patient with slowly equalized severe hyponatremia – a case report - Rudnicka-Czerwiec, Julia; Bartosik-Psujek, Halina (European Journal of Clinical and Experimental Medicine, 2019)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction. Osmotic demyelination syndrome (ODS), or central pontine myelinolysis (CPM), is a complication of severe and prolonged hyponatremia, particularly when hyponatremia is corrected too rapidly. However, even slow correction of hyponatremia can result in ODS. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Aim. In this paper, we describe a patient who developed ODS following slow correction of hyponatremia. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Description of the case. This article describes a case of chronic hyponatremia occurring in the course of alcoholism. The patient was admitted in severe condition with extremely low sodium level. Electrolyte supplementation was carried out according to the European Renal Best Practice (ERBP) guidelines; however, there was a rapid increase in sodium level leading to the development of symptomatic osmotic demyelinating syndrome. Following several weeks of rehabilitation and supplementation of B vitamins, the patient’s condition gradually improved. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Sodium deficiency should be equilibrated very carefully, especially in patients with chronic hyponatremia in the course of alcoholism. Even small doses of sodium administered in accordance with the guidelines in chronic hyponatremia can cause a rapid increase in serum sodium level resulting in osmotic demyelination syndrome.